2013
DOI: 10.1111/apa.12454
|View full text |Cite
|
Sign up to set email alerts
|

Oral sucrose and non‐nutritive sucking goes some way to reducing pain during retinopathy of prematurity eye examinations

Abstract: Although sucrose combined with non-nutritive sucking modestly reduces pain scores during eye examinations, there is need to further studies to explore significant pain relief for infants undergoing retinopathy of prematurity screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 23 publications
(31 reference statements)
0
55
1
2
Order By: Relevance
“…Interestingly, in a randomized controlled study aimed to evaluate the efficacy of oral sucrose and non‐nutritive sucking during ROP screening, Dili et al observed significantly lower PIPP scores in the intervention group, but without changes in physiological variables . Similarly, Kabatas et al found a significant effect of oral paracetamol on PIPP scores but not in physiological parameters …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a randomized controlled study aimed to evaluate the efficacy of oral sucrose and non‐nutritive sucking during ROP screening, Dili et al observed significantly lower PIPP scores in the intervention group, but without changes in physiological variables . Similarly, Kabatas et al found a significant effect of oral paracetamol on PIPP scores but not in physiological parameters …”
Section: Discussionmentioning
confidence: 99%
“…A total of 9 (7.8 %) infants experienced episodes of desaturations and bradycardia without a significant difference between the groups. Oral paracetamol group had a significantly lower PIPP score during examination of the first eye, following insertion of the speculum [12 (9)(10)(11)(12)(13) vs. 14 (13-15), p 0.01] ( Table 2; Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore many pain-relieving procedures are being tested in ROP examination. Recently, Dilli et al found that oral sucrose has a positive effect in reducing pain during ROP screening [13]. Similarly, Costa et al suggested that oral glucose solution is effective for pain relief during ROP examination [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations